Investigation of Always Present and Spectrum Sensing based Incumbent Emulators - Abbas Ali Sharifi (AUT Journal of Electrical Engineering)
Cognitive radio (CR) technology has been suggested for effective use of spectral resources. Spectrum sensing is one of the main operations of CR users to identify the vacant frequency bands. Cooperative spectrum sensing (CSS) is used to increase the performance of CR networks by providing spatial diversity. The accuracy of spectrum sensing is the most important challenge in the CSS process since the sensing performance is vulnerable to security attacks. Primary user emulation attack (PUEA) is one of the most important attacks, where a malicious attacker sends the signal similar to the signal of the legitimate primary user (PU) and deceives the CR sensors to avoid them from accessing the spectrum holes. In this paper, we investigate two different strategies for the attacker. Always present (AP) and spectrum sensing (SS) based strategies. In the AP scenario, the PUEA, without performing spectrum sensing, continuously sends its fake signals. In SS based PUEA, the attacker senses the spectrum to identify the spectrum holes and then only sends its signals in idle frequency bands. Assuming attack strategy, we estimate normalized attack power factor (NAPF) to obtain an optimal value of energy detection threshold. The parameter NAPF is the ratio of the average emitted power of the attacker to the average power of the PU transmitter. The obtained results verify the superiority of the proposed energy detection approach compared to the existing conventional methods.